Evaluating the accuracy of earth rotation parameters based on the BDS observations - Chenxiang Wang; Pengfei Zhang; Tengxu Zhang; Ziyu Shen; Jizhang Sang; Wenbin Shen (Geodesy and Geodynamics)
The BeiDou satellite system (BDS) has progressed with the full operationalization of the second-generation regional system (BDS-2) and the third-generation global system (BDS-3). This technology plays a crucial role in determining Earth Rotation Parameters (ERPs). In this study, we determine the ERPs based on the observations of BDS-2, BDS-3 and BDS-2+BDS-3, with the time spanning from August 18, 2022, to August 18, 2023. The IERS EOP 20C04 series is used as a reference to evaluate the accuracy of the ERP estimates. We analyze the impact of different numbers of reference stations, polyhedron volumes, observation arc lengths, satellite types, and satellite systems on solving ERPs using BDS-2 and BDS-3 observation data provided by the International GNSS Service (IGS) stations. When selecting a specific satellite type, it is necessary to choose an appropriate observation arc length based on different numbers of reference stations while maximizing the volume of the formed polyhedron to achieve optimal efficiency and accuracy in parameter estimation. When both the number of reference stations and observation arc length are fixed, higher precision of the ERPs can be achieved using observations from MEO than MEO + IGSO and MEO + IGSO + GEO. Moreover, when considering only IGSO and MEO satellites as options for analysis purposes, BDS-3 provides higher accuracy compared to BDS-2. In summary, when using BDS for ERP estimation and MEO satellite observations with the same observation arc length, selecting stations from reference stations with larger polyhedral volumes can significantly improve the efficiency and accuracy of parameter estimation.